Implementasi Model Poin Counter Point untuk Meningkatkan Motivasi dan Hasil Belajar Bahasa Indonesia Siswa di SMP Negeri 4 Mataram - Siti Sumiati (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
This study aims to analyze the application of the Point Counter Point learning model (opinion debate) in an effort to increase students' motivation and learning outcomes in Indonesian. This research method uses classroom action research which is carried out in two cycles, each activity cycle is; planning, implementation, observation and reflection. The subjects of this study were students of class VIII-2 SMP Negeri 4 Mataram, totaling 32 people. This research instrument uses observation, documentation and tests. While the data analysis technique used descriptive analysis. The results of this study indicate that the application of the Point Counter Point model (opinion debate) can increase students' motivation and learning outcomes. The research data shows that the average score of students' learning motivation in the first cycle (3.38), while in the second cycle (4.31), while the learning outcomes in the first cycle (66.67) and cycle II (79.86) have exceed the established success indicators.